Frataxin an Anti-Tumour Protein, Activates Oxidative Metabolism to the Detriment of Ketolysis, Regulation of SCOT-OXCT1 - Israël, Maurice; Berg, Eric; Tenenbaum, Guy (British Journal of Healthcare and Medical Research, 2024)
Friedreich’s ataxia is a genetic disease caused by a mutation in the gene (FXN chromosome 9). It is an excessive repetition of the GAA codon, which prevents the expression of the frataxin protein. This protein ensures the functioning of the respiratory complexes of the mitochondria, by providing them with the iron/sulfur clusters they need to conduct electrons to oxygen and ensure oxidative metabolism. Frataxin also activates aconitase in the Krebs cycle, which thus acts as a switch for citrate directed to the cycle and energy production, or to the cytosol and the synthesis of fatty acids. In its inactive form, aconitase then intervenes in the mobilization of iron. The stimulation of oxidative metabolism by frataxin has an anti-cancer effect, because oxidative metabolism puts ketolysis and SCOT to rest, in cells that have become dependent on this sole source of acetyl-CoA. Conversely, the drop in frataxin in ataxia is carcinogenic, because the drop in oxidative metabolism initiates ketolysis, in cells that have become SCOT dependent, particularly if OXCT1 produces sufficient SCOT, to compensate for the accelerated proteolysis of SCOT, due to the decrease in frataxin, which binds to SCOT and protects it from the proteasome.